Determination of coefficient of rate of horizontal consolidation of peat soil - Gofar, Nurly (Universiti Teknologi Malaysia, 2006)
Encountered extensively in wetlands, fibrous peat is considered as problematic soil because it exhibits unusual compression behavior. When a mass of fibrous peat soil with both vertical and horizontal drainage boundaries is subjected to a consolidation pressure, rate of excess pore water dissipation from the soil in the horizontal direction (ch) is expected to be higher than that in the vertical direction (cv). ch/cv of two is commonly used in practice for estimation of consolidation in soft clay improved by vertical drain whereas published data showed that the ch/cv ratio for fibrous peat could be as high as 300. This research focused on the consolidation behavior of fibrous peat from Kampung Bahru, Pontian, Johor with respect to one-dimensional vertical and horizontal consolidation. The result is useful for evaluation of the utilization of some type of vertical drainage for soil improvement to accelerate the settlement of fibrous peat soil. Results from constant head permeability reveal that the soil is almost isotropic as indicated by equal initial permeability in horizontal and vertical direction. Hydraulic consolidation tests in Rowe cell, the coefficient of rate of horizontal consolidation increases significantly with consolidation pressure, while the increase in the coefficient of rate of vertical consolidation does not increase as much. The ch/cv ratio increase from 3.5 to 6 for consolidation pressure of 25 to 200 kPa. The ratio of coefficient of permeability kh/kv under a consolidation pressure of 200 kPa is about 5. This finding implies that the utilization of horizontal drain maybe suitable for accelerating settlement and reducing the effect of secondary consolidation.